The Comparative Reliability and Feasibility of the Past-Year Canadian Diet History Questionnaire II: Comparison of the Paper and Web Versions - Geraldine Lo Siou (Nutrients, 2017)
Advances in technology-enabled dietary assessment include the advent of web-based food frequency questionnaires, which may reduce costs and researcher burden but may introduce new challenges related to internet connectivity and computer literacy. The purpose of this study was to evaluate the intra- and inter-version reliability, feasibility and acceptability of the paper and web Canadian Diet History Questionnaire II (CDHQ-II) in a sub-sample of 648 adults (aged 39–81 years) recruited from Alberta’s Tomorrow Project. Participants were randomly assigned to one of two groups: (1) paper, web, paper; or (2) web, paper, web over a six-week period. With few exceptions, no statistically significant differences in mean nutrient intake were found in the intra- and inter-version reliability analyses. The majority of participants indicated future willingness to complete the CDHQ-II online, and 59% indicated a preference for the web over the paper version. Findings indicate that, in this population of adults drawn from an existing cohort, the CDHQ-II may be administered in paper or web modalities (increasing flexibility for questionnaire delivery), and the nutrient estimates obtained with either version are comparable. We recommend that other studies explore the feasibility and reliability of different modes of administration of dietary assessment instruments prior to widespread implementation.